Low dose ketamine versus morphine for acute severe vaso occlusive pain in children: a randomized controlled trial - Lubega, Felix Anthony; Munube, Deogratias; Tumukunde, Janat; Nkwine, Rita; Nabukenya, Mary T.; Luggya, Tonny S. (Scandinavian Journal of Pain, 2018)
Acute pain episodes associated with sickle cell disease (SCD) are very difficult to manage effectively. Opioid tolerance and side effects have been major roadblocks in our ability to provide these patients with adequate pain relief. Ketamine is cheap, widely safe, readily available drug, with analgesic effects at sub-anesthetic doses and has been used in wide range of surgeries, pediatric burns dressing change and cancer related pain however, literature concerning its use in sickle cell crises is still limited in our setting. This study aimed to establish if 1 mg/kg of intravenous ketamine is non inferior to intravenous morphine 0.1 mg/kg in severe SCD-associated pain. We performed an institutional review board-approved randomized, prospective, double-blinded, active-control, non-inferiority trial at the national referral sickle cell center. Children between 7 and 18 years of age with severe painful sickle cell crisis, defined by numerical rating scale score of greater or equal to 7 were enrolled. Patients were consented and randomized to receive, either IV ketamine (LDK) 1 mg/kg or IV morphine (MOR) 0.1 mg/kg as an infusion over 10 min. The primary endpoint is maximal change in Numerical Rating Scale (NRS) pain score. Secondary outcomes were, incidence of adverse effects, optimal time to and duration of action of ketamine and incidence of treatment failures by treatment group. A clinically meaningful difference in validated pain scores was defined as 1.3 units. Assuming both treatments are on average equal, a sample size of 240 patients (120 per group) provided 95% power to demonstrate that IV LDK is non-inferior to IV morphine with a 0.05 level of significance and a 10% non-inferiority margin. All analyses were based on a modified intention to treat. This trial was registered with clinicaltrials.gov NCT02434939. Two hundred and forty patients were enrolled (LDK120, MOR120). Demographic variables and baseline NRS scores (8.9 vs. 9.2) were similar. LDK was comparable to MOR in the maximum change in NRS scores, 66.4% vs. 61.3% (MD 5.5; 95% CI −2.2 to −13.2). Time to achieve maximum reduction in NRS pain scores was at 19.8 min for LDK and 34.1 min for MOR. The average duration of action for LDK was 60 min. MOR had more patients still at maximum effect at 120 min (45.8% vs. 37.5%; RR 1.2; 95% CI 0.9–1.7). LDK patients were 11.3 times more likely to develop side effects, though were transient, anticipated and non-life threatening (37.5% vs. 3.3%). MOR had significantly more treatment failures 40% vs. 28.3% (RR 0.7; 95% CI 0.5–1.03, p=0.07) Vital signs and sedation scores were similar in both groups. Intravenous LDK at 1 mg/kg provides comparable analgesic effectiveness as IV MOR in the acute treatment of severe painful sickle cell crisis in children in the day care sickle cell center. However, it is associated with a high incidence of several transient, non-life threatening mild side effects.